Mutations of NFKBIA, encoding IκBα, are a recurrent finding in classical Hodgkin lymphoma but are not a unifying feature of non-EBV-associated cases - Lake, A; Shield, L; Cordano, P; Chui, D; Osborne, J; Crae, S; Wilson, K; Tosi, S; Knight, S; Gesk, S; Siebert, R; Hay, RT; et al. (2009)
A consistent feature of the Hodgkin and Reed-Sternberg (HRS) cells in classical Hodgkin lymphoma (cHL) is the constitutive activation of NF-κB transcription factors. In Epstein-Barr virus (EBV)-associated cases of cHL, expression of viral antigens most probably leads to NF-κB activation but for non-EBV-associated cases, the mechanism is not clear. Previous small studies have demonstrated deleterious mutations of NFKBIA, the gene encoding IκBα, in HRS cells. In the present study, we aimed to establish the frequency of NFKBIA mutation in cHL by investigating a larger series of cases and to determine whether these mutations are a characteristic feature of non-EBV-associated cHL. Single HRS cells from 20 cases of cHL were analysed by PCRs covering all 6 exons of the gene. Clonal deleterious mutations were detected in 3 cases and in 1 case both alleles of the gene were shown to harbour mutations. NFKBIA mutations were detected only in non-EBV-associated cases but the majority of these cases had wild-type NFKBIA. It remains possible that defects in genes encoding other inhibitors of NF-κB, such as TNFAIP3 (A20) and CYLD, are involved in the latter cases, as described for one case in this series. © 2009 UICC.